Pembinaan Sanitasi dan Penggunaan Alat Pelindung Diri (APD) Pedagang Makanan Terhadap Jumlah Pengunjung di Malioboro Yogyakarta - Sri Haryanti; Narto Narto; Hikmah Nurul Avida; Adhy Timur Hartanto (Fakultas Teknik, 2023)
Good snack food production is very beneficial for small and large scale food industry to produce quality food, suitable for consumption and safe for health, and Good Food Production for household industry (IRT) needs to be applied to household scale industry. This is inseparable from the role of traders in serving buyers or visitors who Hygienes and meets the rules of food sanitation.Food safety efforts through sanitation development and using personal protective equipment (PPE) for food traders in jalan Malioboro can also increase the number of tourist visits to the city of Yogyakarta. The problem found in the field is that during a pandemic like today, food traders in serving visitors pay less attention to sanitation and do not use Personal Protective Equipment (PPE). The purpose of this study is to determine the description of the use of PPE and can determine the effect of food sanitation development with the application of the use of Personal Protective Equipment (PPE) for food traders in Malioboro Street. The research method uses experiments with one group Pretest-Post test design research design. Stages by providing guidance on sanitation and the use of Personal Protective Equipment (PPE) then analyzed the number of visitors before and after coaching using statistical analysis of One Way Anova test. Based on the results of the study, it is known that the level of knowledge is less than 6 traders (10.72%), moderate knowledge is as much as 27 traders (48.21%). Then after given guidance sanitation hygiene sanitation traders 49 (87.5%) qualified. the analysis results obtained that the test results obtained sig value (pvalue) 0.000. The value is smaller than the alpha of 0.05 / 0.01, which means there is a significant difference in the treatment of the use of PPE against the number of visitors (H0 is rejected and Ha is accepted)